Eosinophil cationic protein levels parallel coagulation activation in the blister fluid of patients with bullous pemphigoid. (20th March 2014) - Tedeschi, A.; Marzano, A.V.; Lorini, M.; Balice, Y.; Cugno, M.
Abstract: Background: Bullous pemphigoid (BP) is an autoimmune blistering disease due to autoantibodies against two hemidesmosomal antigens, namely BP180 and BP230, and characterized by coagulation activation both at cutaneous and systemic levels. Skin‐infiltrating eosinophils contribute to bulla formation and, upon activation, are supposed to initiate the coagulation cascade. Objective: The aim of this study was to investigate whether the activation of eosinophils and coagulation are linked in BP. Methods: We evaluated the correlation between eosinophil cationic protein (ECP) levels and concentrations of the prothrombotic markers F1 + 2 and D‐dimer in blister fluid and blood samples of 30 BP patients. Thirty healthy subjects were used as normal controls. Results: ECP, F1 + 2 and D‐dimer plasma levels were significantly higher in BP patients than in normal subjects. A significant correlation was found between ECP plasma levels and blood eosinophil count ( r  = 0.54, P  = 0.002). F1 + 2 plasma levels positively correlated with disease severity, expressed as the percentage of body surface area involved ( r  = 0.36, P  = 0.048). A striking increase in ECP (288.8 ± 45.2 ng/mL), F1 + 2 (31 409.9 ± 2929.4 pmol/L) and D‐dimer levels (342 798.3 ± 44 206 ng/mL) was found in blister fluid from BP patients. In blister fluid, ECP levels were significantly higher than in peripheral blood ( P  < 0.0001) and were positively correlated with the levels of both F1 + 2 ( r  = 0.4, P  = 0.02) and D‐dimer ( r  = 0.5, P  = 0.0045). Conclusions: ECP levels are strikingly elevated in blister fluids from BP patients and correlate with markers of coagulation activation, supporting the view that eosinophils initiate the coagulation cascade at skin level.